SYSTEMATIC LITERATURE REVIEW: KEPUTUSAN PEMBELIAN PADA WARUNG MAKAN DI JEMBER - Oktaviansyah, Renaldy Dwi; Fatimah, Feti; Rahayu, Jekti (Fakultas Ekonomi dan Bisnis, 2022)
This study discusses the factors that influence consumer purchasing decisions at restaurants in Jember. By using a systematic literature review method consisting of three stages, namely, planning, implementation, and reporting. The research data was obtained from Google Scholar published in 2014 to 2021, the initial research found in this study was 438 articles, and the total research used was 12 articles as data sources and will be analyzed further. This study only uses research with a quantitative approach. The results of a systematic literature review of all published studies state that the factors that influence consumer purchasing decisions at restaurants in Jember are very diverse, namely, Store Atmosphere, product, price, promotion, place, Taste, Service Quality, Facilities, advertising, and lifestyles. The main factor that influences is the place where consumers are not likely to find products that are outside the reach of consumers. The location factor is also a factor that determines the success of a business. Place strategy is one of the most important determinants in consumer behavior, companies must choose a strategic location in placing their shop (restaurant) in an area / area close to crowds and community activities.